Efektivitas Pembelajaran Berbantuan Augmented Reality Terhadap Peningkatan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Rahmanda, Rasnida (STKIP Taman Siswa Bima, 2025)
This study aims to analyze the effectiveness of Augmented Reality (AR)-assisted learning in enhancing the critical thinking skills of elementary school students. The research was motivated by the need for pedagogical innovation capable of stimulating higher-order thinking skills in accordance with 21st-century educational demands. A quantitative approach employing a quasi-experimental method with a Non-Equivalent Control Group Design was used, involving 60 fifth-grade students from two elementary schools in East Jakarta, divided into experimental and control groups. The research instrument was a critical thinking skills test developed based on Facione’s five indicators: interpretation, analysis, evaluation, inference, and explanation. The results revealed that AR-assisted learning significantly improved students’ critical thinking abilities compared to conventional instruction. The experimental group’s posttest mean score reached 78.6, an increase of 20.3 points from the pretest, with an N-Gain value of 0.61 (moderate–high category) and a Cohen’s d effect size of 1.52 (large effect). The analysis per aspect indicated the highest improvement in analytical and inferential skills. Overall, the integration of AR in learning proved effective in creating interactive, contextual, and reflective learning experiences that strengthened students’ scientific reasoning processes. These findings affirm that AR serves as a potent educational medium supporting the implementation of the Merdeka Curriculum through the reinforcement of critical thinking competence and digital literacy among elementary students.